Preparation and characterization of BiVO4powder by the sol-gel method - Pusit Pookmanee (2018)
Bismuth vanadate (BiVO 4 ) powder was successfully prepared by the sol-gel method. Bismuth nitrate and ammonium vanadate were used as the starting precursors with mole ratio of 1:1 in ethanol media at 70°C for 1 h. The yellow gel was calcined at 400-600°C for 2 h. The phase of BiVO 4 powder was characterized by X-ray diffraction (XRD). The morphology and chemical composition of BiVO 4 powder were investigated by scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDXS). The functional groups of BiVO 4 powder was identified by Fourier transform infrared spectroscopy (FTIR) and the surface area of BiVO 4 powder was determined by Brunauer, Emmett and Teller technique (BET). © 2013 Copyright Taylor and Francis Group, LLC.